PENGARUH PENAMBAHAN SARI JERUK NIPIS TERHADAP SIFAT SENSORIS SELAI TOMAT (Lycopersicum esculentum Mill.) - Tandikura, Defyanti T.; Lalujan, Lana E.; Sumual, Maria Fransisca (Fakultas Pertanian, Universitas Sam Ratulangi, 2019)
Abstract Jam is a semi-solid or thick food made from 45 parts weight of fruit pulp and 55 parts weight of sugar. The basic ingredients of jam include fruit pulp, sugar, citric acid and pectin. Tomato is a horticultural product that is very easily damaged. One alternative to processing tomatoes is by making it to be a jam. Tomatoes contain pectin and acids so that they are eligible for making jam. Lime is a fruit that contains citric acid which is often used as a flavor enhancer and source of natural acids in food and beverage products. The purpose of this study was to determine the concentration of lime juice in making tomato jam based on sensory properties. The research method used was Completely Randomized Design with the treatment of adding lime juice with different concentrations. Sensory testing of tomato jam with the parameters of color, taste, smell and texture that are preferred and have easy topical power is sample B (2%) which has a moisture content of 23.93%, acidity (pH) 4.12, total acid 0, 78% and vitamin C 32.65 mg / 100 g.Keywords: Jam, Tomato, Lime